Les barrages hydroélectriques au Brésil : contraintes et violences - Guillaume Leturcq (Les Cahiers ALHIM)
In the context of economic growth and new environmental preoccupations Brazil is faced with, the electricity produced by dams is a key element. The dams disturb the environment (economical, social and ecological) of the rural societies that live nearby. Moreover, these dams are always responsible for the migrations of their victims (atingidos) and also somes differents violences. Violences are divided into two forms: symbolics or physics. They are several and do not touch to the same degree the families. It is mainly about violence going towards the families living close to the dam, emitted by the company which builds the dam or of indirects actors.